Heterogeneous Receptors - Based Molecule Harvesting in MC: Analysis for ISI Mitigation and Energy Efficiency - Huang, Xinyu; Huang, Yu; Wen, Miaowen; Yang, Nan; Schober, Robert (IEEE Transactions on Communications, 2024)
This paper establishes a molecule harvesting transmitter (TX) model in molecular communication (MC). In particular, we consider that molecules are encapsulated in vesicles generated within the TX and released from the TX through membrane fusion process. We also consider that the TX membrane is covered by heterogeneous receptors of varying sizes and at arbitrary locations, where the receptors can absorb the released molecules once the molecules hitting any of the receptor. Assuming that the vesicle generation follows a jump process, with each vesicle generated at distinct time instants, and assuming a transparent receiver (RX), we calculate the molecule release rate, the expected fraction of absorbed molecules at the TX, and the received signal at the RX. All obtained analytical expressions are functions of all receptors' locations and sizes, and are validated by particle-based simulations. Our numerical results indicate that evenly distributed receptors on the TX membrane absorb more molecules than randomly distributed receptors or a single receptor. Furthermore, inspired by the biological phenomenon that cells can regulate their release of new molecules by interacting with the molecules that are already present in the environment, we incorporate a negative feedback mechanism (NFM) at the TX. This mechanism utilizes the number of molecules absorbed by the TX as a criterion to determine if the TX should stop releasing additional molecules. We then derive the closed-form expression for the expected fraction of recyclable molecules for a single emission. Here, the pool of recyclable molecules comprises both the molecules that remain unreleased by the TX due to NFM and those that are absorbed back by the TX. Our numerical results demonstrate that incorporating NFM can reduce inter-symbol interference (ISI) while maintaining the same peak received signal as without NFM. Additionally, our results show that TXs incorporating both molecule harvesting and NFM can achieve a higher energy efficiency and lower error probability than TXs employing only molecule harvesting or neither functionality.
CRIS-Team Scopus Importer:2024-09-20
Keywords: channel impulse response; energy efficiency; heterogeneous receptors; inter-symbol interference mitigation; Molecular communication; molecule harvesting